Knowledge Level of Doctors in USU Medical School Regarding Doctor-Patient Communication - Chailes, Andre; T. Ibnu Alferraly (Talenta Publisher, 2022)
Background. While carrying out its duties, doctors certainly cannot be separated from the act of communicating with patients. Doctor-patient communication is defined as ongoing communication between doctors, as a medic, with the patient as the treated person. This communication skills are important and therefore must be mastered by doctors. But before that, doctors must have adequate knowledge of how to communicate properly and effectively with patients. Lack of this communication skill will be a serious problem so it should not be ignored. Objective. To determine the doctors level of knowledge about doctor-patient communication. Methods. This study was conducted in descriptive with cross sectional approach. The data were collected by distributing the questionnaire of 15 questions to 71 doctors who were still actively teaching at Faculty of Medicine, Universitas Sumatera Utara. The collected data then analyzed using SPSS computer program. Results. The results showed that most of the doctor that work on Faculty of Medicine, Universitas Sumatera Utara, 83.1% of the samples were in good category of knowledge, 14.1% of the samples were in sufficient category of knowledge, the rest 2.8% of the samples were in low category of knowledge. Conclusion. Majority of the doctor have a good level of knowledge about doctor-patient communication. Keyword: Communication, Doctor-Patient, Knowledge, Skills